2022
DOI: 10.1002/emp2.12779
|View full text |Cite
|
Sign up to set email alerts
|

Development of a low‐dimensional model to predict admissions from triage at a pediatric emergency department

Abstract: Objectives This study aims to develop and internally validate a low‐dimensional model to predict outcomes (admission or discharge) using commonly entered data up to the post‐triage process to improve patient flow in the pediatric emergency department (ED). In hospital settings where electronic data are limited, a low‐dimensional model with fewer variables may be easier to implement. Methods This prognostic study included ED attendances in 2017 and 2018. The Cross Indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 57 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…The consistent superiority of ML models in determining and prioritizing patients within the ED setting holds the potential to redefine triage precision [23,24,30,34,42,[44][45][46]. Reduced instances of under-triaging and over-triaging, coupled with the remarkable decrease in erroneous triage rates for critically ill patients, underscore the impact on the accuracy of patient prioritization [25,29].…”
Section: Hospital or Intensive Care Unit Admissionmentioning
confidence: 98%
See 4 more Smart Citations
“…The consistent superiority of ML models in determining and prioritizing patients within the ED setting holds the potential to redefine triage precision [23,24,30,34,42,[44][45][46]. Reduced instances of under-triaging and over-triaging, coupled with the remarkable decrease in erroneous triage rates for critically ill patients, underscore the impact on the accuracy of patient prioritization [25,29].…”
Section: Hospital or Intensive Care Unit Admissionmentioning
confidence: 98%
“…The Another study reported the development of a low-dimensional ML model to predict whether a patient would be admitted or discharged from the pediatric ED, resulting in an area under the receiver operating characteristic curve (AUROC) of 0.853 [24]. They concluded that early prediction of admission and discharge probabilities during the ED triage process could be utilized to enhance patient flow and contribute to more effective bed management.…”
Section: Triage Efficiencymentioning
confidence: 99%
See 3 more Smart Citations